Training and Telling Experience How to Make Eco-Friendly and Healthy Soap at Pondok Pesantren Hirzu Millati Singocandi Kudus - Arina Hafadhotul Husna; Rohmatun Nafi’ah (Jurnal Pengabdian Kesehatan, 2022)
The increasing number of Covid-19 cases that are getting out of control, especially in the Kudus area, Central Java, has forced the community to play a role in efforts to reduce the number of Covid-19 transmissions. Washing hands with soap is one of the steps that can break the chain of transmission of the Covid-19 virus, however, the wastewater produced by SLS which contained in soap has increased significantly due to the increasing use of soap which damage the environment. This community service activity aims to provide soft skill training on how to make eco-friendly and healthy soap and English training on "Genre Recount–text" to practice speaking skills. The target of this activity is the female students of the Hirzu Millati Kudus Islamic Boarding School. This activity hold on Friday, January 9, 2021, with 3 stages of implementation; planning, preparation, and implementation stages. The method implemented was a lecture with presentation technique, soap making practice carried out directly, and speaking practice carried out with an easy and fun method. The results of this community service activity are very good. The positive impact resulting from this community service activity is that female students become more creative, productive and have awareness to care about the environment. In addition, the presentation of their experiences during the activation process with "Genre–Text" adds insight and knowledge of their English language so that they become more confident in the Speaking application.